STUDI EMPIRIS DETERMINASI HARGA MINYAK DUNIA DI INDONESIA - Triana, Neni; fauzan; irfan; Sayed Shadli (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2022)
This study aims to analyze the effect of inflation on world oil prices, Rupiah-US Dollar exchange rate on world oil prices, money supply on world oil prices, world oil prices on inflation, Rupiah-US Dollar exchange rate on inflation, money supply on inflation, world oil prices against the Rupiah-US Dollar exchange rate, inflation against the Rupiah-US Dollar exchange rate, the money supply against the Rupiah-US exchange rate, world oil prices against the money supply, inflation against the money supply, and the Rupiah-US Dollar exchange rate against the money supply outstanding in the short and long term. Data sources were obtained from BPS Indonesia 2021, Bank Indonesia 2021, and Investing.com, 2021. The data analysis method used was panel data regression analysis through Vector Error Correction Model (VECM) estimation. The results show that: (1) Inflation has a positive effect on world oil prices in the long term, but inflation has no effect on world oil prices in the short term; (2) The Rupiah-US Dollar Exchange Rate has a positive effect on world oil prices in the long term, but the Rupiah-US Dollar Exchange Rate has no effect on world oil prices in the short term; (3) The money supply has a negative effect on world oil prices in the long and short term; (4) World oil prices have a negative effect on inflation in the long and short term; (5) The Rupiah-US Dollar Exchange Rate has a positive effect on inflation in the long and short term; (6) The money supply has a negative effect on inflation in the long term and short term; (7) World oil prices have a negative effect on the long-term and short-term US Dollar exchange rate; (8) Inflation has a positive effect on the Rupiah-US Dollar exchange rate in the long term, but inflation has a negative effect on the Rupiah-US Dollar exchange rate in the short term; (9) The money supply has a negative effect on the Rupiah-US Dollar exchange rate in the long term, but the money supply has a positive effect on the Rupiah-US Dollar exchange rate in the short term; (10) World oil prices have a negative effect on the long-term and short-term US Dollar exchange rate; (11) Inflation has a positive effect on the money supply in the long run, but it has a negative effect on the money supply in the short term; (12) The Rupiah-US Dollar exchange rate has a positive effect on the money supply in the long run, but the Rupiah-US Dollar exchange rate has a negative effect on the money supply in the short term.